PELATIHAN PENGELOLAAN ADMINISTRASI PENDIDIKAN BERBASIS DIGITAL BAGI TENAGA KEPENDIDIKAN DI MA SWASTA SE KECAMATAN CIBUNGBULANG - Rahmawati, Ima; Soeganda, Bintang Caraka; Lestar, Hana (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
The digital based educational administration training for education staff at private Islamic senior high schools (MA) in Cibungbulang District aimed to enhance technical competencies and attitudes toward technology use. This study employed a descriptive qualitative approach with a participatory action research model involving 32 participants from five schools. Data were collected through observation, interviews, documentation, and pre–post training questionnaires, and analyzed using descriptive statistics and thematic analysis. Results indicated a 32% average increase in digital competence, particularly in cloud based file management, automated reporting, and online communication. Participants also demonstrated positive attitude changes, shifting from initial reluctance to sustained motivation in adopting digital systems. Supporting factors included infrastructure readiness, school leadership support, and participant enthusiasm, while key challenges were limited devices and unstable internet connectivity. The program produced a replicable training model adaptable to local contexts, with implications for strengthening efficient, transparent, and technology adaptive education management.